2021
DOI: 10.1177/1753193420981871
|View full text |Cite
|
Sign up to set email alerts
|

Hand osteomyelitis in arterial calcification, diabetes mellitus and end-stage renal failure: a comparison of 210 cases over 12 years

Abstract: We present 210 patients with hand osteomyelitis in 246 rays over 12 years, including detailed analysis of 29 patients in this cohort with digital artery calcification evident on plain X-ray. Overall 71 patients had diabetes mellitus and/or end-stage renal failure, including 28 of 29 patients with calcification. In the calcification group, 17 patients had ipsilateral arteriovenous fistulae, five had steal syndrome and 15 had digital ulceration or skin necrosis. Compared with 181 controls, patients with calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Confounding variables, including diabetes mellitus and peripheral vascular disease, which are associated with systemic inflammation and elevated inflammatory markers even in the absence of infection, were prevalent among patients requiring amputation (33/64 [52%] and 15/64 [23%] respectively). 31 - 34 Our study found that 43 of the 48 patients (90%) with either diabetes mellitus or end-stage renal failure had elevated CRP at diagnosis, compared with 46/73 (63%) without.…”
Section: Discussionmentioning
confidence: 64%
“…Confounding variables, including diabetes mellitus and peripheral vascular disease, which are associated with systemic inflammation and elevated inflammatory markers even in the absence of infection, were prevalent among patients requiring amputation (33/64 [52%] and 15/64 [23%] respectively). 31 - 34 Our study found that 43 of the 48 patients (90%) with either diabetes mellitus or end-stage renal failure had elevated CRP at diagnosis, compared with 46/73 (63%) without.…”
Section: Discussionmentioning
confidence: 64%
“…Understanding poor prognosticators may be helpful in counseling patients and treating infections. A retrospective analysis of 210 patients with osteomyelitis of the hand showed that, when arterial calcification was present, there were increased risks of polymicrobial infection, additional surgical procedures, and delayed digital amputation, and a higher mortality rate at 1 and 5 years 45 . Thus, early amputation in patients with arterial calcification may optimize disease-free survival.…”
Section: Infectionmentioning
confidence: 99%
“…2 Many of these pathologies manifest in patients requiring dialysis due to the increased presence of arterial calcification and steal syndrome. 3,4 As a result, approximately 5% of patients with end-stage renal disease (ESRD) will develop symp-tomatic upper extremity ischemia. 5 In those who present with fingertip ischemia eventually requiring UEA, high mortality has been described.…”
Section: Introductionmentioning
confidence: 99%
“…5 In those who present with fingertip ischemia eventually requiring UEA, high mortality has been described. 4,6 Conservative management of nonhealing fingertip wounds includes lifestyle modification, pharmacotherapy to increase blood flow and treat infections, and local wound care. 2 Patients nonresponsive to these treatments may require more invasive intervention in the form of operative wound debridement, revascularization, or reconstruction using skin grafting, skin substitutes, or local/free tissue transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation